Analisis Tujuan Pendidikan Islam dalam Al-Qur'an - Hamdan (Multiverse: Open Multidisciplinary Journal, 2022)
This short article aims to analyze the Educational Objectives contained in the QS. Al-Baqarah: 31, QS. An-Naml: 40, and QS. Al-Mujadalah:11. The discussion of this research is to prioritize the literature of the Qur'an al-Karim by taking one of its own themes that will be discussed. For this reason, the author takes the thematic interpretation research methodology or Maw'? Tafsir. The commentators usually use several references or sources of interpretation in interpreting the Qur'an where the source is used for explanations or as a treasury of interpretation, so that the results of the interpretation have the original intent of the verse being interpreted, or as a comparison of interpretation. For this reason, the primary data sources in this discussion are the verses of the Qur'an which contain the Educational Goals including QS. Al-Baqarah: 31, QS. An-Naml: 40, and QS. Al-Mujdah:11. Which of course has a munasabat in it, both between verses in one letter, as well as between verses with different letters in the Qur'an al-Kar?m. Then the data is supported by secondary data, this data is obtained from the hadiths of the prophet related to the topic of discussion, the history of the companions and tabi'?n, the opinions of the previous commentators, and books related to the topic of discussion. which is the focus of the main discussion of educational goals according to the Qur'an contained in Al-Baqarah: 31, An-Naml: 40, and Al-Mujlah:11. These three verses will be linked with the munasabah verse with other verses. The results of the interpretation of the three verses contain educational goals. The three verses contain content that the purpose of Islam ic education is to potential humans, humanize humans and position humans